2023
DOI: 10.1021/acs.jpcc.3c04544
|View full text |Cite
|
Sign up to set email alerts
|

Quantifiable Surface Methoxy Groups on Zr(OH) Groups of UiO-66 Metal–Organic Framework: Generation from Methanol-13C and Reactivity

Daniel Dittmann,
Julia Schröder,
Elif Kaya
et al.

Abstract: We herein conduct the first 1 H and 13 C MAS NMR investigations that explore the formation of surface methoxy groups (SMG) on defect Zr(OH) groups of UiO-66 metal−organic frameworks. Loading acetone-2-13 C indicates that UiO-66 contains weakly acidic Zr(OH) groups. These react at room temperature with adsorbed methanol-13 C to SMG. Quantitative formation of SMG and methanol removal are achieved at 473 K. 1 H− 13 C heteronuclear correlation proves close proximity between persistent, inaccessible Zr(OH) groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Acetone-2- 13 C has in particular been loaded on zeolites and zeotypes ZSM-5, ,,, Y, ,,, MOR, ZSM­12, ZSM-22, MAPO-5, MAPO-34, amorphous silica-alumina, ,, [Al]­MCM-41, , [Sn]­MCM-41, [Sn]­Beta, [Sn]­SSZ-13, on γ-Al 2 O 3 , , on TiO 2 (anatase), on heteropoly acid H 3 PW 12 O 40 , ,, on pure and sulfated SnO 2 and ZrO 2 , on MoO 3 /SnO 2 , on pure, MoO x - and WO x -loaded ZrO 2 , on acidic metal salts (mainly halogenides at low temperature), and on UiO-66 hydroxyl groups. , Acetone-2- 13 C reacts at room temperature on acid sites mainly via aldol condensation. ,,,,,, The 13 C MAS NMR peaks caused by the reaction products are usually of no further relevance for the interpretation; however, they cause often confusion and shall thus be addressed. In particular, NMR peaks of diacetone were identified around δ 13C = 209 and 73 ppm, of mesityl oxide at δ 13C = 210 and 188 ppm, and of isophorone and mesitylene around δ 13C = 210, 180, 138, and 34 ppm. , On [Sn]­Beta, supported by 119 Sn MAS NMR spectra, gem -diol-type intermediates giving rise to a slim peak at δ 13C = 76 ppm were reported .…”
Section: Families Of Solid-state Nmr Probe Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Acetone-2- 13 C has in particular been loaded on zeolites and zeotypes ZSM-5, ,,, Y, ,,, MOR, ZSM­12, ZSM-22, MAPO-5, MAPO-34, amorphous silica-alumina, ,, [Al]­MCM-41, , [Sn]­MCM-41, [Sn]­Beta, [Sn]­SSZ-13, on γ-Al 2 O 3 , , on TiO 2 (anatase), on heteropoly acid H 3 PW 12 O 40 , ,, on pure and sulfated SnO 2 and ZrO 2 , on MoO 3 /SnO 2 , on pure, MoO x - and WO x -loaded ZrO 2 , on acidic metal salts (mainly halogenides at low temperature), and on UiO-66 hydroxyl groups. , Acetone-2- 13 C reacts at room temperature on acid sites mainly via aldol condensation. ,,,,,, The 13 C MAS NMR peaks caused by the reaction products are usually of no further relevance for the interpretation; however, they cause often confusion and shall thus be addressed. In particular, NMR peaks of diacetone were identified around δ 13C = 209 and 73 ppm, of mesityl oxide at δ 13C = 210 and 188 ppm, and of isophorone and mesitylene around δ 13C = 210, 180, 138, and 34 ppm. , On [Sn]­Beta, supported by 119 Sn MAS NMR spectra, gem -diol-type intermediates giving rise to a slim peak at δ 13C = 76 ppm were reported .…”
Section: Families Of Solid-state Nmr Probe Moleculesmentioning
confidence: 99%
“…However, based on the available literature, it is suggested that rather strongly adsorbed methanol gave rise to this signal. 1 H MAS NMR chemical shifts of methyl group protons are found at δ 1H = 3.8 ± 0.2 ppm. ,, Methanol interacts surprisingly strong with the surface, and thus the desorption of excess methanol must be performed at elevated temperatures. , As a too high temperature will lead to methanol dehydration to DME, an intermediate methylation and desorption temperature of 393 K or below is suggested, while temperatures above 400 K are discouraged. , Note that recycle delay times up to 30 s were applied for quantitative measurements of SMG. , X-ray powder diffraction data on methanol adsorbed in ZSM-5 micropores are provided elsewhere , Physisorbed methyl iodide gives peaks at δ 13C = −18 to −25 ppm, far distant from the chemical shift range of SMG .…”
Section: Families Of Solid-state Nmr Probe Moleculesmentioning
confidence: 99%
See 1 more Smart Citation